Intelligent Edge Caching and Computing for Scalable Information Systems - Zhang, Yu-Dong (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: In scalable information systems, edge computing can help to overcome the challenges of latency, bandwidth, and connectivity in large-scale networks by reducing the amount of data that needs to be transmitted over the network. OBJECTIVES: The edge devices, such as sensors, cameras, gateways, routers, switches, multiplexers, integrated access devices, etc., can perform initial data processing and filtering, reducing the data volume sent to the central system. METHODS: This special issue aims to provide the recent progress of intelligent edge caching and computing for scalable information systems. RESULTS: The guest editors received more than 30 submissions, and finally, ten papers were accepted. CONCLUSION: This special issue has contributed to advancing academic research and practice in intelligent edge caching and computing for scalable information systems.